Rational Design and Synthesis of 1‐(Arylideneamino)‐4‐aryl‐1H‐imidazole‐2‐amine Derivatives as Antiplatelet Agents. (1st June 2017) - Amidi, Salimeh; Esfahanizadeh, Marjan; Tabib, Kimia; Soleimani, Zohreh; Kobarfard, Farzad
Abstract: Based on previous studies indicating the pharmacophoric role of a hydrazone group and azole rings for antiplatelet aggregation activity, a few series of compounds with both hydrazone and an azole (imidazole) ring in their structures were synthesized, and their platelet aggregation inhibitory effects were evaluated. Two of these 1‐(arylideneamino)‐4‐aryl‐1 H ‐imidazole‐2‐amine derivatives, compounds4 a [( E )‐1‐(benzylideneamino)‐4‐phenyl‐1 H ‐imidazol‐2‐amine] and4 p [( E )‐4‐phenyl‐1‐((thiophen‐2‐ylmethylene)amino)‐1 H ‐imidazol‐2‐amine], exhibited IC50 values similar to that of acetylsalicylic acid against collagen as a platelet aggregation inducer. Structural comparison of the synthesized compounds revealed that those with a para ‐substituted phenyl ring on the imidazole were among the most active compounds against platelet aggregation induced by arachidonic acid (AA), and the presence of a thiophene ring in these compounds maximized their antiplatelet activity. Abstract : Put a ring on it : Cyclization of aromatic guanylhydrazones with phenacyl bromide was found to increase the antiplatelet activity against arachidonic acid (AA) and collagen as platelet aggregation inducers. Phenyl ring substituents at imidazole position 4 decreased activity against collagen‐induced aggregation, whereas a para ‐substituted phenyl ring on the imidazole increased activity against AA‐induced aggregation. Changes did not affect adenosine diphosphate (ADP)‐induced platelet aggregation.